Electron Paramagnetic Resonance (EPR) Study of Spin-Labeled Camptothecin Derivatives: A Different Look of the Ternary Complex - Ricci, Antonio (J Med Chem, 2011)
Camptothecin (CPT) derivatives are clinically effective poisons of DNA topoisomerase I (Top1) able to form a ternary complex with the Top1–DNA complex. The aim of this investigation was to examine the dynamic aspects of the ternary complex formation by means of site-directed spin labeling electron paramagnetic resonance (SDSL-EPR). Two semisynthetic CPT derivatives bearing the paramagnetic moiety were synthesized, and their biological activity was tested. A 22-mer DNA oligonucleotide sequence with high affinity cleavage site for Top1 was also synthesized. EPR experiments were carried out on modified CPT in the presence of DNA, of Top1, or of both. In the last case, a slow motion component in the EPR signal appeared, indicating the formation of the ternary complex. Deconvolution of the EPR spectrum allowed to obtain the relative drug amounts in the complex. It was also possible to demonstrate that the residence time of CPT “trapped” in the ternary complex is longer than hundreds of microseconds.